Impact of Feeder Access and Stocking Density on Tail Injuries and Performance in Weaned Piglets - Anne Maria Stevina Huting; Francesc Molist; Piet van der Aar (Animals, 2025)
The effects of stocking density (SD) and feeder access (FA) on the performance and damaging behaviour of weaned piglets are not well understood. Three experiments (Ts) were conducted. T1 compared low SD (LSD) (0.55 m2/piglet) and moderate SD (MSD) (0.37 m2/piglet), T2 compared low FA (LFA1) (1.33 piglets/feeder; partially slatted floor) and high FA (HFA1) (0.66 piglets/feeder; fully slatted floor), and T3 compared LFA2 (2.33 piglets/feeder) and HFA2 (1.00 piglets/feeder). T1 included 24 replicates, while T2 and T3 each had 12 replicates. In total, 576 piglets were weighed at days (d) 0, 14, and 35 post-weaning (PW). Faecal consistency (FC) was recorded multiple times per week. Tail and ear injuries were scored at d35 PW. Piglets housed under LSD grew faster throughout the experiment (p < 0.05) and had a lower feed conversion ratio (FCR) between d0 and 14 PW (p = 0.02) than those in MSD. Tail injuries were not significantly affected (p = 0.14). HFA1 piglets had higher FC between d0 and 14 PW (p = 0.01) and overall (p = 0.02), but fewer intact tails at d35 PW (p = 0.01) compared with LFA1. In T3, LFA2 piglets had a lower average daily gain (p = 0.03), higher FCR between d14 and 35 PW (p = 0.04), and fewer intact tails (p < 0.01) than HFA2 piglets. These results suggest that both FA and SD can influence piglet performance, FC, and damaging behaviour.